COVID Alert: Factors Influencing the Adoption of Exposure Notification Apps Among Canadian Residents - Oyibo, Kiemute; Morita, Plinio Pelegrini (Frontiers in Digital Health, 2022)
The continued emergence of new variants of COVID-19 such as the Delta and Omicron variants, which can cause breakthrough infections, indicates that contact tracing and exposure notification apps (ENAs) will continue to be useful for the long haul. However, there is limited work to uncover the strongest factors that influence their adoption. Using Canada’s “COVID Alert” as a case study, we conducted an empirical, technology-acceptance study to investigate the key factors that account for users’ intention to use ENAs and the moderating effect of important human factors. Our path model analysis shows that four factors significantly influence the adoption of COVID Alert among Canadian residents: perceived risk, perceived usefulness, perceived trust, and perceived compatibility. The overall model explains over 60% of intention to use, with type of design, use case, and adoption status moderating the strength of the relationships between the four factors and intention to use. We discuss these findings and make recommendations for the design of future ENAs.